PERSEPSI KONSUMEN TERHADAP GREEN MARKETING STARBUCKS MALL BOEMI KEDATON LAMPUNG - Nina Lelawati; Nani Septiana; Rahmat Fajar Ramdani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Abstract Environmental responsibility is a consumer perception of environmentally friendly management, particularly for a business. Environmental issues are becoming a new problem in the era of marketing.Green marketing can be a bad way to get people to buy from you.